The Armed Pashtun: The Smuggling of Small Firearms to the Frontier (1890-1914) - Giunchi, Elisa (Oriente moderno, 2022)
Afghanistan is the country in the world with the most SALW (small arms and light weapons). Contrary to what is usually assumed, the proliferation of modern firearms in the country did not start in the 1980s, but at the end of the 19th century, when Pashtun tribes acquired modern rifles and ammunition through a variety of means, mostly through smuggling. The paper investigates the illegal arms trade from the Gulf to the north-western Indian Frontier, an area of crucial importance for British imperial strategists and the Government of India, at a time of great power rivalry and a relative decline of Britain’s global influence.